Despliegue óptimo de redes inalámbricas para la infraestructura de medición inteligente de energía eléctrica - Quel Novillo, Santiago Xavier (2015)
In this document we present an optimization model of the base stations that serve as collection points for data that are sent from the smart meters in order to cover a group of users that are grouped in a residential area, which sends Data collected by the distribution companies taking control data of energy consumption in each area where the user is located. In the article, we propose the method ILP and two heuristic methods of cluster users who are the K-Means method and the method of K-Medoids for each base station is required to install in the area. The article presents a comparison between the three algorithms we propose for the grouping of users to discuss which of the clustering methods have less coverage error, less time and better clustering performance so you can see which of the three methods is applied more efficient with the use of graphics. With the optimization of base stations we can get a glimpse of how many BS (base stations) we will install in the real way ruling out other SB that were proposed initially as candidates, resulting in a cost minimization installation and an intelligent network that is efficient, reliable and economical with the main objective is to cover all users, or people who are in the area who benefit from the mains.